Contratos interadministrativos: caracterização e aspectos de seu regime jurídico - Almeida, Pericles Ferreira de (2019)
The Dissertation studies the inter-administrative contracts, trying to highlight that the agreements between public entities are true administrative contracts. Therefore, promotes a brief analyses of the traditional models of contract in public law, represented by the French and German systems, as well as the lines of evolution of the general theory of administrative contract, still ongoing, taking the foreign experience to better understand Brazilian law. Thereafter, it demonstrates the inadequacy of traditional conceptions in the Brazilian doctrine of inter-administrative contracts, built on administrative covenants and legal figures considered of the same nature, in particular, refuting its framing as a non-contractual agreement or complex act. Then, the study systematizes the various modalities of inter-administrative contracts, for each of the categories raised offering examples located in the current positive law. Taking the results of this stage, it investigates the proximity of the legal regime of inter-administrative contracts with that of administrative contracts with individuals, first taking care of the formation phase of inter-administrative contracts and then the problem of previous bidding, after that, taking care of the execution phase of these contracts and the question of the applicability of exorbitant clauses. The conclusion reached is that the study of conventional relations between public administrations belongs to the general theory of administrative contracts